Geological Position, Structural Manifestations of the Elbistan Earthquake and Tectonic Comparison of Two Strongest 06.02.2023 Seismic Events in Eastern Turkiye - Trikhunkov, Ya. I.; Celik, H.; Lomov, V. S.; Trifonov, V. G.; Bachmanov, D. M.; Karginoglu, Y.; Sokolov, S. Yu. (Pleiades Publishing Inc, 2024)
The Elbistan (Chardak) earthquake with magnitude M-w = 7.5 or 7.6 happened in Eastern Anatolia on 06.02.2023 at 10:24 UTC, following the strongest in the region of East Anatolian (Pazarc & imath;k) earthquake with M-w = 7.8 which occurred on the same day at 1:17 UTC to the south of the region. The Elbistan earthquake activated adjacent segments of the Chardak and Uluova faults with left-lateral strike-slip displacements. The resulting seismic ruptures have a total length of 190 km, of which 148 km are represented by sinistral lateral slip. Their maximum amplitude of 7.84 m was recorded 8 km east of the epicenter. The strike-slip seismic ruptures of the Elbistan and East Anatolian earthquakes represent exposure of their focal zones on the land surface. Both earthquakes exceed average values of these parameters for continental earthquakes of strike-slip type in terms of focal zone sizes and amplitudes of seismic displacements. At the same time, both sources do not propagate deeper than the upper part of the crust (16-20 km). Ophiolite assemblages covering the same depths are widely spread in the area of focal zones of both earthquakes. Two maxima were found in the distribution of seismic strike-slip displacement along the epicentral zone of the Elbistan earthquake (i) amplitudes of 5.7-7.84 m in the Chardak fault zone and (ii) amplitudes of 3.5-5.1 m in the Uluova fault zone. Both maxima coincide with the areas of ophiolites or their contacts with basement rocks. In crystalline basement rocks, the sinistral strike-slip amplitudes are significantly reduced. We attribute the increased values of focal zone sizes and displacement amplitudes of both earthquakes to the rheological features of ophiolites, which increase a possibility rocks slipping during seismic movements. We explain the fact that the sources of both earthquakes cover only the upper part of the crust by the uplift of the top of rocks with reduced P-wave velocities, including the upper mantle and the lower part of the crust, and interpret them as heated rocks with reduced strength.
Keywords: Elbistan earthquake; Eastern Anatolian earthquake; Chardak and Uluova active fault zones; seismogenic displacements; sinistral strike-slip fault; ophiolites; depth of focal zone; basement; Earth's crust